Achieving band convergence by tuning the bonding ionicity in n‐type Mg3Sb2. Issue 18 (19th March 2019) - Sun, Xin; Li, Xin; Yang, Jiong; Xi, Jinyang; Nelson, Ryky; Ertural, Christina; Dronskowski, Richard; Liu, Weishu; Snyder, Gerald J.; Singh, David J.; Zhang, Wenqing
Abstract : Identifying strategies for beneficial band engineering is crucial for the optimization of thermoelectric (TE) materials. In this study, we demonstrate the beneficial effects of ionic dopants on n‐type Mg3 Sb2 . Using the band‐resolved projected crystal orbital Hamilton population, the covalent characters of the bonding between Mg atoms at different sites are observed. By partially substituting the Mg at the octahedral sites with more ionic dopants, such as Ca and Yb, the conduction band minimum (CBM) of Mg3 Sb2 is altered to be more anisotropic with an enhanced band degeneracy of 7. The CBM density of states of doped Mg3 Sb2 with these dopants is significantly enlarged by band engineering. The improved Seebeck coefficients and power factors, together with the reduced lattice thermal conductivities, imply that the partial introduction of more ionic dopants in Mg3 Sb2 is a general solution for its n‐type TE performance. © 2019 Wiley Periodicals, Inc. Abstract : The covalent interaction between different Mg sites at the conduction band minimum of Mg3 Sb2 is revealed by band‐resolved projected crystal orbital Hamilton populations.